Genetic variation and recombination analysis of PRRSV-2 GP3 gene in China from 1996 to 2023 - Lv, Chen; Zheng, Yajie; Liu, Kexin; Li, Gan; Luo, Qin; Zhang, Hang; Sha, Huiyang; Wang, Ruining; Kong, Weili; Zhao, Mengmeng (Frontiers in Microbiology, 2024)
Porcine reproductive and respiratory syndrome virus (PRRSV) has become widespread in China particularly the highly pathogenic porcine reproductive and respiratory syndromes (HP-PRRSV), NADC30, and NADC34 strains, and has posed a threat to the swine industry for over 20 years. To monitor genetic variation in PRRSV-2 GP3 strains in China, we analyzed 618 strains isolated between 1996 to 2023 and constructed phylogenetic trees. Additionally, 60 selected strains were used to analyze nucleotide and amino acid homology. PRRSV GP3 gene exhibited nucleotide identity ranging from 78.2% to 100.0% and amino acid similarity ranging from 74.9% to 99.6%. The GP3 gene in the 60 selected strains consisted of 254 amino acids, and amino acid mutations in the strains primarily occurred in B-cell epitopes, T-cell epitopes, and highly variable regions. The glycosylation sites of the strains used for amino acid sequence comparisons remained unaltered, except for the N 29 site in the GD20220303-2022 strain. PRRSV-2 strains in China belong to lineages 1, 3, 5, and 8. Recombination analysis detected two recombination events, involving lineages 1 and 8. Overall, this study investigated multiple strains of the PRRSV-2 GP3 gene, highlighting their prevalence and genetic diversity in China. These results offer a foundational basis for clinical prevention strategies and vaccine development.